2015
DOI: 10.1177/0898264315585504
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status Across the Life Course and Cognitive Function Among Older Adults

Abstract: Childhood SES and adult SES both had relationships with cognitive status and, to a lesser degree, change in cognition in later life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
125
2
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 163 publications
(158 citation statements)
references
References 46 publications
18
125
2
3
Order By: Relevance
“…The attenuated effect sizes for the monozygotic twins compared with the dizygotic twins further strengthened these conclusions. The findings in this study challenge the causality of the association between childhood social class and cognitive abilities found in previous research (4,14,18,19). Kendler et al (11) found evidence of both genetic and environmental influences on early adult (age 18 y) cognitive performance in their study of home-reared and adopted-away siblings.…”
Section: Discussioncontrasting
confidence: 39%
“…The attenuated effect sizes for the monozygotic twins compared with the dizygotic twins further strengthened these conclusions. The findings in this study challenge the causality of the association between childhood social class and cognitive abilities found in previous research (4,14,18,19). Kendler et al (11) found evidence of both genetic and environmental influences on early adult (age 18 y) cognitive performance in their study of home-reared and adopted-away siblings.…”
Section: Discussioncontrasting
confidence: 39%
“…The index included measures of parent's education (1 = 8 or more years of education; 0 = otherwise), father's occupation (1 = white-collar occupation; 0 = otherwise), and financial well-being at childhood (1 = average or well-off; 0 = poor). Respondents who had missing data on parent's education and father's occupation were coded as 0 based on preliminary analyses showing that respondents in this category had similar characteristics with respondents in the lowest category [8]. After the childhood SES index was created, it was dichotomized at the median (1 = above median; 0 = at or below the median).…”
Section: Independent Variablesmentioning
confidence: 99%
“…Childhood SES was ascertained with four retrospective questionnaire items: father's education, mother's education, father's occupation, and family financial well-being during childhood [8]. Father's education and mother's education variables were based on a set of dichotomous measures from respondent's self-report of parent's educational attainment (eight or more years of education (reference), less than eight years of education, and missing).…”
Section: Independent Variablesmentioning
confidence: 99%
See 2 more Smart Citations